2015
DOI: 10.1007/s12253-015-9998-4
|View full text |Cite
|
Sign up to set email alerts
|

L744,832 and Everolimus Induce Cytotoxic and Cytostatic Effects in Non-Hodgkin Lymphoma Cells

Abstract: Non-Hodgkin Lymphoma (NHL) constitutes a very heterogeneous group of diseases with different aggressiveness. Diffuse large B-cell lymphoma (DLBCL) and Burkitt's lymphoma (BL) are two clinically aggressive lymphomas from the germinal center, very heterogeneous and with different genetic signatures. Several intracellular pathways are involved in lymphomagenesis, being BCR/PI3K/AKT/mTOR and RAS/RAF pathways the most frequently ones. In this context the therapeutic potential of a mTOR inhibitor--everolimus--and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…To evaluate the immunological state of an individual, we used the blood collected in the field to make blood smears in the lab, followed by staining [ 44 ]. White blood cell counts and identification (100 cells per smears) were performed using a Nikon Eclipse Ni microscope (Nikon Instruments Europe B.V., Amsterdam, Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the immunological state of an individual, we used the blood collected in the field to make blood smears in the lab, followed by staining [ 44 ]. White blood cell counts and identification (100 cells per smears) were performed using a Nikon Eclipse Ni microscope (Nikon Instruments Europe B.V., Amsterdam, Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…A Ras/Raf pathway inhibitor, L744,832, induces cytotoxicity and cell death in DLBCL and Burkitt’s lymphoma cells. 38 It is possible that RASIP1 plays its lymphoma-promoting role by interacting with Ras. Meanwhile, RASIP1 has been demonstrated to bind to Rap1 15 , and regulate Cdc42 39 , suggesting that RASIP1 may function by regulating other molecules.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a limited number of studies are available on the efficacy and tolerance of EVL in the context of oncological diseases and pediatric LT, but there is adequate information available for adult patients. Animal and preclinical studies have shown anti-tumor effects of mTORi [21,22]. mTORi are already being used as a second-line treatment for renal cell carcinomas [14] as well as for advanced pancreatic neuroendocrine tumors [23] .…”
Section: Discussionmentioning
confidence: 99%